2009
DOI: 10.1158/0008-5472.can-09-2067
|View full text |Cite
|
Sign up to set email alerts
|

Activating Peroxisome Proliferator-Activated Receptor γ Mutant Promotes Tumor Growth In vivo by Enhancing Angiogenesis

Abstract: Peroxisome proliferator-activated receptor γ (PPARγ) is expressed in a variety of cancer cells. The addition of ligand activates the receptor by inducing a conformational change in the receptor, which can be recapitulated by mutation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 49 publications
3
42
0
Order By: Relevance
“…Similarly, rosiglitazone was shown to inhibit mouse lung tumor cell growth and metastasis in vivo through direct and indirect anti-angiogenic effects [82] . Although the above studies reveal important anticancer effects for PPARγ ligands, it is important to note that PPARγ signaling has also been associated with tumor promoter activity in some cancer cells such as colon and breast, and that this effect was linked to increased β-catenin, c-Myc, Angptl4 and Wnt 5 expression [83][84][85] (Table 1). PPARγ ligands enhanced 7,12-dimethylbenz(a)anthracene-induced rat mammary adenocarcinoma [86] and promoted colonic tumor growth in Apc Min mice fed a high-fat diet [87] .…”
Section: Pparγ and Angiogenesismentioning
confidence: 99%
“…Similarly, rosiglitazone was shown to inhibit mouse lung tumor cell growth and metastasis in vivo through direct and indirect anti-angiogenic effects [82] . Although the above studies reveal important anticancer effects for PPARγ ligands, it is important to note that PPARγ signaling has also been associated with tumor promoter activity in some cancer cells such as colon and breast, and that this effect was linked to increased β-catenin, c-Myc, Angptl4 and Wnt 5 expression [83][84][85] (Table 1). PPARγ ligands enhanced 7,12-dimethylbenz(a)anthracene-induced rat mammary adenocarcinoma [86] and promoted colonic tumor growth in Apc Min mice fed a high-fat diet [87] .…”
Section: Pparγ and Angiogenesismentioning
confidence: 99%
“…ANGPTL4 has been implicated in regulation of angiogenesis [23,24,25,26,27,28]. Unlike angiopoietin 1, 2, and 4, ANGPTL4 exerts its effect independent of the TIE receptor family (TIE1 and TIE2) [54].…”
Section: Discussionmentioning
confidence: 99%
“…While ANGPTL4, a secreted glycoprotein encoded by the ANGPTL4 gene, is well known for its role in lipid metabolism [14,15,16,17,18,19,20,21,22], it is also thought to mediate angiogenesis with both anti- and pro-angiogenic effects [23,24,25,26,27,28,29]. ANGPTL4 has been reported to inhibit vascular permeability, tumor cell motility, invasiveness [30,31], sprouting [32], tubule-like structure formation [32,33,34,35], and vascular leakiness [31,34].…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral neuroprotection produced by PPARc agonists could be due to any of several mechanisms including oxidative stress modulation (Collino et al 2006), anti-inflammatory effects (Collino et al 2006;Sundararajan et al 2005), induction of mitochondrial biogenesis (Strum et al 2007) and/or through neuronal up-regulation of Bcl-2 (Fuenzalida et al 2007). In addition, several recent studies have shown that PPARc agonists reduce damage in cerebral ischemia by inhibition of matrix metalloproteinase-9 Wang et al 2009) or by enhancement of angiogenesis (Chu et al 2006), although the effects of PPARc agonists on angiogenesis in general are unclear and may vary between models and dosing regimes since both promotion (Biscetti et al 2008(Biscetti et al , 2009aTian et al 2009) and inhibition (Aljada et al 2008;Park et al 2009;Scoditti et al 2010) of angiogenesis have been reported following PPARc agonist administration.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the beneficial effects of PPARc agonists have been demonstrated in different animal models of CNS disorders such as multiple sclerosis (Diab et al 2004), global ischemia-induced hippocampal injury ) and focal ischemia-induced brain damage (Shimazu et al 2005;Luo et al 2006;Tureyen et al 2007;Chu et al 2006). The mechanism(s) underlying the beneficial effects of these agents is still unclear, but could be due to actions such as down-regulation of the inflammatory response (Sundararajan and Landreth 2004), upregulation of antioxidant enzymes (Shimazu et al 2005), regulation of cytokine production (Storer et al 2005;Xu et al 2008) or promotion of angiogenesis (Biscetti et al 2008(Biscetti et al , 2009aTian et al 2009). While the neuroprotective potential of PPARc agonists in ischemia is largely unexplored, the presence of PPARc receptors has been reported in the brain of CD1 mice (Cristiano et al 2005) and PPARc knockout mice have been shown to have increased susceptibility to ischemic brain damage (Zhao et al 2009).…”
Section: Introductionmentioning
confidence: 99%